A simulation model for predicting three-dimensional surface morphology in ultra-precision roll die turning. Issue 1 (September 2016) - Qu, Da; Zhang, Peng; Qiao, Zheng; Wu, Dongxu; Wang, Bo
Abstract This paper presents a model for simulating optical surface morphology in ultra-precision roll die turning. Some influencing factors including machining parameters, tool geometry, workpiece parameters, and two directional relative motions between tool and workpiece are considered. The method of elaborating surface morphology is based on mesh of scattering and recombining matrixes depending on time. For verifying the simulation model, a series of experiments is carried out. The simulation results are in good agreement with the measurement results obtained by an atomic force microscope. Then, the influence ofZ directional vibration on surface roughness was analyzed. Furthermore, the influence of amplitude and frequency of two directional vibrations on roughness was also analyzed by the simulation. The reason for badness on machined surface was made clear. Discussion on the difference between the frequency of vibration and surface section was put into effort. This model is helpful to decrease the roughness and improve surface quality by means of vibration adjustment of the tool and to choose optimal processing parameters by simulations.